(untitled) (Confluenţe Bibliologice, 2020)
The study aims to discover the history and art of Bellu Cemetery through the work , Art and Funerary Architecture at Bellu Cemetery” by Oana Marinache. Among historians, architects and their families,G. Bezviconi, is the one who left us the most important information about Bellu Cemetery. He gathered materials, information from members of the boyar families, being interested in presentation of the categories of funerary monuments, styles adopted in the construction of various mortuary monuments, tombs of famous families.